Burst Spinal Cord Stimulation Increases Peripheral Antineuroinflammatory Interleukin 10 Levels in Failed Back Surgery Syndrome Patients With Predominant Back Pain. Issue 4 (13th February 2017) - Kinfe, Thomas M.; Muhammad, Sajjad; Link, Carolina; Roeske, Sandra; Chaudhry, Shafqat R.; Yearwood, Thomas L.
Abstract : Objectives: Burst spinal cord stimulation (SCS) has been reported to reduce back pain and improve functional capacity in Failed Back Surgery Syndrome (FBSS). However, its mechanism of action is not completely understood. Systemic circulating cytokines have been associated with the development of chronic back pain. Methods: This prospective, feasibility study enrolled 12 refractory FBSS patients with predominant back pain (70% of overall pain) suitable for Burst SCS. Back and leg pain intensity (back pain [VASB ]/leg pain [VASL ]), functional capacity (sleep quality [PSQI]), depressive symptoms (BDI), body weight, stimulation parameters, and plasma levels of pro‐inflammatory (Il‐1b; TNF; HMGB1)/anti‐inflammatory (Il‐10) cytokines were collected at baseline and after three months of Burst SCS and compared to healthy controls. Results: Pain intensity (pre VASB : 8.25 ± 0.75 vs. post 1.42 ± 1.24) and functional capacity (PSQI: pre 7.92 ± 3.92 vs. post 3.42 ± 1.24; BDI: pre 20.83 ± 3.56 vs. post 10.92 ± 0.75) significantly improved compared to baseline. Pro‐inflammatory HMGB1 remained unchanged (preburst: 3.35 ± 3.25 vs. postburst: 3.78 ± 3.83 ng/mL; p  = 0.27; W  = −30) versus the HC group (2.53 ± 2.6 ng/mL; p  = 0.47; U  = 59), while anti‐inflammatory IL‐10 levels were significantly elevated after burst SCS as compared to baseline (preburst 12.54 ± 22.95 vs. postburst 43.16 ± 74.71 pg/mL; p  = 0.03; W = −48) and HC group (HC: 7.03 ± 11.6 vs. postburst 43.16 ± 74.71 pg/mL; p  = 0.03; W  = −48; p  = 0.04). Baseline preburst IL‐10 values and preburst VASB significantly correlated (Spearman correlation r  = −0.66; p  = 0.05; 95 CI −0.86 to −0.24), while correlation was not significant between postburst IL‐10 values and postburst VASB (Spearman correlation r  = −0.49; p  = 0.18; 95 CI −0.83 to −0.15). Postburst IL‐10 values correlated significantly with postburst PSQI scores (Spearman correlation r  = −0.66; p  = 0.05; 95 CI −0.86 to −0.24), while no correlation was found between preburst and postburst changes related to the BDI. Conclusions: Burst SCS increased systemic circulating anti‐inflammatory IL‐10, improved FBSS back pain and back pain associated co‐morbidities like disrupted sleep architecture and depressive symptoms in FBSS patients. Thus, suggesting a possible relationship between burst SCS and burst‐evoked modulation of peripheral anti‐inflammatory cytokine IL‐10 in chronic back pain.